Factors associated with HIV testing among youth in Tanzania based on the 2016-2017 Tanzania HIV Impact Survey (THIS) - Yan Wang; Janni J. Kinsler; Sylvia Kiwuwa-Muyingo (Public Library of Science (PLoS), 2022)
HIV testing continues to be a challenge among the young population in Tanzania. As of 2017, only 30% of 15-19-year-olds reported getting tested and receiving their results. This study will examine the demographic and socio-behavioral characteristics associated with HIV testing among adolescents and young adults in Tanzania. Interview data from the 2016-2017 Tanzania HIV Impact Survey (THIS) were analyzed on 10,128 adolescents and young adults 15-24 years of age, representing 10.5 million youth in Tanzania. Weighted logistic regression was used to model the relationship of HIV testing with demographic and socio-behavioral characteristics. Half (50%) of respondents reported ever having been tested for HIV. HIV testing was significantly lower among males compared with females (AOR = 0.5;95% confidence interval [CI] = 0.5-0.6; p<0.001), 15-19 year olds compared with 20-24 year olds (AOR = 0.4;95% CI = 0.4-0.5; p<0.001), no education compared with secondary or post-secondary education (AOR = 0.4;95% CI = 0.3-0.6; p<0.001), rural residents compared with urban residents (AOR = 0.7;95% CI = 0.6-0.9; p<0.001) and those who don't use condoms during sexual intercourse compared with those who do (AOR = 0.6;95% CI = 0.5-0.8; p<0.001). Among HIV-infected youth, younger age group, rural residents, education less than primary, single, high income, and sex workers were significantly associated with never testing for HIV. This study highlights the majority of characteristics affecting HIV testing among young people in Tanzania have not changed over the years, thus it is necessary to re-examine the current approaches to HIV testing. The COVID-19 pandemic will add to this challenge as it collides with the ongoing HIV epidemic and competes for needed medical supplies and health care provider resources. In light of this current situation, intensified and targeted HIV testing programs for at risk young populations in Tanzania should be prioritized.